2016
DOI: 10.1074/jbc.m116.720193
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Histone Readout by the Dual Plant Homeodomain (PHD) Fingers of Rco1 Mediates Rpd3S Chromatin Recruitment and the Maintenance of Transcriptional Fidelity

Abstract: The plant homeodomain (PHD) finger is found in many chromatin-associated proteins and functions to recruit effector proteins to chromatin through its ability to bind both methylated and unmethylated histone residues. Here, we show that the dual PHD fingers of Rco1, a member of the Rpd3S histone deacetylase complex recruited to transcribing genes, operate in a combinatorial manner in targeting the Rpd3S complex to histone H3 in chromatin. Although mutations in either the first or second PHD finger allow for Rpd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 31 publications
5
31
0
Order By: Relevance
“…Eaf3 contains a chromo domain that recognizes H3K36me2/3 [9094], and Rco1 contains a dual plant homeodomain (PHD) finger motif that is necessary for chromatin engagement [95] and a homo-dimerization domain [96]. Both PHD fingers are essential for chromatin binding and Rpd3S function, and both domains prefer to bind the unmodified N-terminus of H3 [97]. Interestingly, Rco1 exists as a dimer within the Rpd3S complex, adding two additional chromatin contacts to the complex [96].…”
Section: Effector Proteins That Interact With Unmodified or Methylatementioning
confidence: 99%
See 2 more Smart Citations
“…Eaf3 contains a chromo domain that recognizes H3K36me2/3 [9094], and Rco1 contains a dual plant homeodomain (PHD) finger motif that is necessary for chromatin engagement [95] and a homo-dimerization domain [96]. Both PHD fingers are essential for chromatin binding and Rpd3S function, and both domains prefer to bind the unmodified N-terminus of H3 [97]. Interestingly, Rco1 exists as a dimer within the Rpd3S complex, adding two additional chromatin contacts to the complex [96].…”
Section: Effector Proteins That Interact With Unmodified or Methylatementioning
confidence: 99%
“…Like Set2, Rpd3S can be recruited to chromatin via the phosphorylated CTD of RNAPII, specifically the Ser2/Ser5 dually phosphorylated form [98, 99]. However, without Eaf3 binding to H3K36me2/3, or without the PHD fingers of Rco1, the Rpd3S complex is catalytically inactive [95, 97]. Recent work has suggested that H3K36me stimulates a conformational change in Rpd3S that increases its affinity for chromatin, perhaps stimulating its enzymatic activity [100].…”
Section: Effector Proteins That Interact With Unmodified or Methylatementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, ScRpd3S only decorates coding regions and employs Ser5-phosphorylated polymerase II and Set2-methylated histone H3 to suppress intragenic transcription (46). Interestingly, a recent report shows that the dual PHD fingers of ScRco1 recognize the unmodified N terminus of H3, which restricts the recruitment of ScRpd3S to promoter histones normally carrying H3K4me3 marks (47). Of note, CaRco1 also contains two PHD fingers, and all residues critical for ScRco1 function are conserved in CaRco1 (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The arrangement of nucleosomes and histone PTMs at genomic target regions influences the function of multivalent PTM-binding proteins. The combined contribution of the PHD finger domain in Rco1 and the chromodomain in Eaf3 direct the histone deacetylase complex Rpd3S to active loci that are enriched H3K36me ( 58 , 110 ). Hu et al .…”
Section: Multivalent Histone-binding Domains Integrate Multiple Ptm Smentioning
confidence: 99%